Connexin 43 dephosphorylation at serine 282 induces spontaneous arrhythmia and increases susceptibility to ischemia/reperfusion injury - Lulin Wu; Tianhui Jiang; Zhiping Fu; Luqi Wang; Hongjie You; Jingyi Xue; Dali Luo (Heliyon, 2023)
Background: Connexin 43 (Cx43), the predominant gap junction protein in hearts, is modified by specific (de)phosphorylation events under physiological and pathological states to affect myocardium function and structure. Previously we found that deficiency in Cx43 S282 phosphorylation could impair intercellular communication and contribute to cardiomyocyte apoptosis by activating p38 mitogen-activated protein kinase (p38 MAPK)/factor-associated suicide (Fas)/Fas-associating protein with a novel death domain (FADD) pathway, which is involved in myocardium injury in ischemia/reperfusion (I/R) heart. In addition, mutant at Cx43 S282 substituted with alanine heterozygous mice (S282A+/−) exhibited different degrees of ventricular arrhythmias and only some underwent myocardium apoptosis. In this study, we aimed to investigate the role of Cx43 pS282 in different cardiac pathological phenotypes. Methods: We examined cardiac function, structure, and relevant protein expression in S282A+/− mice (aged 2, 10 and 30 weeks) by electrocardiograph, echocardiography, histological staining, and co-immunoprecipitation followed by Western blot. Intraperitoneal isoprenaline injection and I/R surgery were applied in S282A+/− mice as external stimulus. 2,3,5-triphenyltetrazolium chloride staining was used for myocardium infarction evaluation. Results: Adult S282A+/− mice (aged 10 and 30 weeks) still exhibited spontaneous arrhythmia. Unlike neonatal stage (aged around 2 weeks), no apoptosis-related manifestations and the activation of p38 MAPK-Fas-FADD apoptotic pathway were observed in adult S282A+/− hearts. S282A+/− neonatal mice with cardiomyocytes apoptosis exhibited more than 60% dephosphorylation at Cx43 S282 than WT mice, while less than 40% S282 dephosphorylation were found in adult S282A+/− mice. In addition, although S282A+/− mice displayed normal cardiac function, they were highly susceptible to isoproterenol-induced ECG alternans and prone to cardiac injury and deaths upon I/R attack. Conclusions: These results reinforce that Cx43 S282 dephosphorylation acts as a susceptibility factor in regulating cardiomyocyte survival and cardiac electrical homeostasis in basal conditions and contributes to myocardium injury in the setting of I/R. Cx43 S282 phosphorylation was competent to induce spontaneous arrhythmias, cardiomyocyte apoptosis and deaths based on the degree of S282 dephosphorylation.